Efficacy of Silver Diamine Fluoride versus Fluoride Varnish in Caries Prevention and Treatment in Deciduous Teeth - Davi Lima da Rocha; Débora Borges da Costa; Halyssya Valadares Martins da Silva; Adylla Calixto Silva; Pollyanna de Ulhôa Santos; Ana Cláudia Garcia Rosa (Dentistry and Medical Research)
This integrative review assessed the efficacy of 5% fluoride varnish (FV) and 38% silver diamine fluoride (SDF) in preventing and treating caries in children and deciduous teeth, particularly in public health and socioeconomically disadvantaged settings. We searched PubMed and Google Scholar databases based on their relevance in evaluating the effectiveness of FV and SDF against caries in deciduous teeth. Joanna Briggs Institute’s Critical Appraisal Tools were employed to select the studies. Some studies showed no significant differences in efficacy between FV and SDF, suggesting that both could be equally effective, depending on the clinical scenario. Other studies have highlighted SDF’s superior performance of SDF in arresting caries in dentin and advanced decay and its antibacterial properties, while FV seems to be particularly effective in enamel remineralization during the early stages of caries. Both FV and SDF are effective in managing caries in children and deciduous teeth and offer significant benefits in the public health context by providing minimally invasive and cost-effective treatment options. The choice between FV and SDF should be tailored to the severity of caries and the specific needs of the child, ensuring that interventions are both practical and accessible, especially for the most vulnerable.